Lymphocytes: Versatile Participants in Acute Kidney Injury and Progression to Chronic Kidney Disease - Cao, Chujin; Yao, Ying; Zeng, Rui (Frontiers in Physiology, 2021)
Background: Acute kidney injury (AKI) remains a major global public health concern due to its high morbidity and mortality. The possibility of progression to chronic kidney disease (CKD) makes it a scientific problem to be solved with lack of effective treatments. Summary: Both innate and adaptive immune systems participate in the inflammatory process during acute kidney injury (AKI), and excessive or dysregulated immune responses play a pathogenic role in renal fibrosis, which is an important hallmark of CKD. Researches on the pathogenesis of AKI and CKD have clarified that renal injury induces the production of various chemokines by renal parenchyma cells or resident immune cells, which recruits multiple-subtype lymphocytes in circulation. Some infiltrated lymphocytes exacerbate injury by proinflammatory cytokine production, cytotoxicity and interaction with renal resident cells, which constructs the inflammatory environment and induces further injury even death of renal parenchyma cells. Others promote tissue repair by producing protective cytokines. In this review, we outline the diversity of these lymphocytes and the mechanisms of them to regulate the whole pathogenic stages of AKI and CKD; discuss the chronological responses and the plasticity of lymphocytes related to AKI and CKD progression; and introduce the potential therapies targeting lymphocytes of AKI and CKD, including the interventions of chemokines, cytokines and lymphocyte frequency regulation in vivo, adaptive transfer of ex-expanded lymphocytes and the treatments of gut microbiota or metabolite regulations based on gut-kidney axis. Key Message: In the process of AKI and CKD, Th cells, innate and innate-like lymphocytes exert mainly pathogenic roles, while DNT cells and Tregs are confirmed to be protective. Understanding the mechanisms by which lymphocytes mediate renal injury and renal fibrosis is necessary to promote the development of specific therapeutic strategies to protect from AKI and prevent the progression of CKD.